Transition of Serotype 35B Pneumococci From Commensal to Prevalent Virulent Strain in Children - Fuji, Naoko; Pichichero, Michael; Ehrlich, Rachel L.; Mell, Joshua Chang; Ehrlich, Garth D.; Kaur, Ravinder (Frontiers in Cellular and Infection Microbiology, 2021)
In our community-based prospective cohort study in young children, we observed a significant increase in pneumococcal serotype 35B nasopharyngeal (NP) commensal colonization during the 2011-2014 timeframe, but these strains were not associated with disease. Beginning in 2015 and continuing through to the present the serotype 35B virulence changed and it became the dominant bacteria isolated and associated with pneumococcal acute otitis-media (AOM) in our cohort. We performed comparative analyses of 250 35B isolates obtained from 140 children collected between 2006-2019. Changes in prevalence, clonal-complex composition and antibiotic resistance were analyzed. 72 (29%) of 35B isolates underwent whole-genome sequencing to investigate genomic changes associated with the shift in virulence that resulted in increased rates of 35B-associated AOM disease. 35B strains that were commensals and AOM disease-causing were mainly associated with sequence type (ST) 558. Antibiotic concentrations of β-lactams and ofloxacin necessary to inhibit growth of 35B strains rose significantly (2006-2019) (p<0.005). However, only isolates from the 35B/ST558 showed significant increases in MIC50 of penicillin and ofloxacin between the years 2006-2014 and 2015-2019 (p=0.007 and p<0.0001). 138 SNPs located in 34 different genes were significantly associated with post-2015 strains. SNPs were found in nrdG (metal binding, 10%); metP and metN (ABC transporter, 9%); corA (Mag2+ transporter, 6%); priA (DNA replication, 5%); and on the enzymic gene ldcB (LD-carboxypeptidase, 3%). Pneumococcal serotype 35B strains became a common NP commensal during 2010-2014, then in 2015 a shift in increasingly caused AOM in young children, associated with changes in genetic composition and antibiotic susceptibility.